2017
DOI: 10.1111/ejn.13624
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar expression of the microRNA miR‐101a and its target Ezh2 contribute to rodent anxiety‐like behaviour

Abstract: A greater understanding of neural mechanisms that contribute to anxiety is needed in order to develop better therapeutic interventions. The current study interrogates a novel molecular mechanism that shapes anxiety-like behavior, demonstrating that the microRNA miR-101a-3p and its target, enhancer of zeste homolog 2 (Ezh2) in the amygdala, contribute to rodent anxiety-like behavior. We utilized rats that were selectively-bred for differences in emotionality and stress reactivity, showing that high novelty resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 68 publications
(99 reference statements)
2
25
0
Order By: Relevance
“…The overexpression of other miRNAs such as miR-17-92, miR-34b also decreased anxiety-like behavior in mice and rats respectively ( Jin et al, 2016;Zhu et al, 2017 ). However, miR-101a-3p-overexpressing adeno-associated viruses (AAVs) in the amygdala increased anxiety-like behavior in the OF and EPM tests of high-novelty-responding (HR) rats ( Cohen et al, 2017 ). Also, miR-155 KO mice exhibited reduced float duration and increased latency to float ( Fonken et al, 2016 ), but, no changes in anxiety-like behavior were observed in miR-132/212 KO mice ( Hernandez-Rapp et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of other miRNAs such as miR-17-92, miR-34b also decreased anxiety-like behavior in mice and rats respectively ( Jin et al, 2016;Zhu et al, 2017 ). However, miR-101a-3p-overexpressing adeno-associated viruses (AAVs) in the amygdala increased anxiety-like behavior in the OF and EPM tests of high-novelty-responding (HR) rats ( Cohen et al, 2017 ). Also, miR-155 KO mice exhibited reduced float duration and increased latency to float ( Fonken et al, 2016 ), but, no changes in anxiety-like behavior were observed in miR-132/212 KO mice ( Hernandez-Rapp et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the above findings suggest that miR‐101a could be a potential diagnostic factor and therapeutic target for hypertensive kidney disease. On the other hand, some other targets of miR‐101a have been previously reported, such as Ezh2 in anxiety behaviour, fosab in zebrafish heart regeneration and so on. However, whether these above miR‐101a's targets are also involved in hypertensive nephropathy needs to be further analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noticed that 1351 miRNAs were from 12 Drosophila species, which accounted for about half of known insect miRNAs (Kozomara and Griffiths-Jones 2014). Many studies to elucidate the functions of miRNAs in regulating a variety of insect physiological processes have been carried out, such as in metamorphosis development (Sokol et al 2008;Gomez-Orte and Belles 2009;Ling et al 2014;Belles 2017;Wu et al 2017), cell growth (Wang et al 2010), behavior (Cohen et al 2017), sex determination (McJunkin and Ambros 2017), oogenesis , embryogenesis (Jannot et al 2016), immunity (Zhu et al 2013), insect-pathogen interactions (Hussain and Asgari 2010;Asgari 2013;Wu et al 2016), etc. Several miRNAs have been reported to regulate insect metamorphosis by targeting genes either in the ecdysone cascade or the JH cascade (Zhang et al 2009;Belles 2017).…”
Section: Introductionmentioning
confidence: 99%